Ide Bunuh Diri sebagai Faktor Risiko Bunuh Diri di Asia: Telaah Sistematis dan Meta-analisis dari Studi Kasus-Kontrol - Cathleen, Fabiola; Ivano Kalaij, Ayers Gilberth; Soelaeman, Muhamad Faza; Raharja, Sarah Latifa (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: Suicide has become the third leading cause of death among individuals in their productive years, underscoring the pressing requirement for effective preventive measures and risk assessment strategies. Earlier studies have indicated that suicidal ideation may play a role as a risk factor of completing suicide. To bolster this understanding, we conducted a systematic review and meta-analysis focusing on the relationship between suicidal ideation and completed suicide within Asian populations. Methods: This review adopted a systematic approach, adhering to the four-phased PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram and checklist. Case-control studies were selected, focusing on samples of individuals aged 15-44 years who had received psychiatric care. Exclusion criteria included language barriers, incomplete or inaccessible texts, publications older than 2000, and participants with co-existing medical conditions that could interfere with the results. To assess the quality and potential bias of the included studies, the Oxford’s Critical Appraisal Skills Programme (CASP) Case-Control Checklist and critical appraisal worksheet were utilized. Result: The search process yielded a total of 641 records, from which six studies were finally included in the meta-analysis. We found a statistically significant association between suicidal ideation and suicide (aOR 4.20; 95%CI 3.00-5.88, p less than 0.00001) with low heterogenity among the studies. The most common bias identified was related to the acceptability of case recruitment. Conclusion: Suicidal ideation can act as a predictor of suicide risk in Asian populations. Incorporating the assessment of suicidal ideation in suicide prevention initiatives is critical for promptly identifying and intervening with individuals at risk.